Analysis of the Implementation of the Sports Achievement Development System in Koni, Kendal Regency - Fitriyani, Ana; Rahayu, Setya; Hartono, Mugiyo (Journal of Physical Education and Sports, 2024)
This research aims to analyze the implementation of the achievement sports development system at KONI Kendal Regency using the 9 pillars of SPLISS Model 2.0. This research used mixed methods. The research sample consisted of 40 athletes, 8 coaches and 10 administrators, consisting of sports administrators, government and non-government sports institutions. Data collection techniques were carried out using interviews, questionnaires, observation and documentation methods. The research results show that from all 9 pillars quantitatively the athlete's score is 65.2% in the quite good category, the coach's score is 68.8% in the quite good category. The conclusions of this research are: 1) Involvement with the private sector, sponsors and the general public provides additional funding support; 2) policy synergy that is not yet aligned; 3) Lack of an effective system in identifying potential athlete talent; 5) The need for increased athlete and post-career support for athletes; 6) There is not yet optimal support for training facilities that support the training of high performance athletes; 7) Competition networks that do not support athlete sustainability. The researchers' suggestions are: 1) There is a need to understand policy strategies in sports funding; 2) There is a need to align sports structures and sports policies; 3) Needs strengthening in aspects of foundation and participation in the development and scouting of athlete talent; 4) Need support and guarantees for sports players; 5) Standardization of sports facilities based on sports science; 6) It is necessary to facilitate certified trainer human resources, and strengthen policies for organizing sustainable competitions;